2022
DOI: 10.1007/s10570-022-04779-0
|View full text |Cite
|
Sign up to set email alerts
|

The tissue dust analysis system: a new device and methodology to quantify dusting and linting propensity in hygiene tissue papers

Abstract: Linting and dusting are commonly used terms to describe the tendency of a tissue web to release unbound and loosely bound bers or ller particles during the tissue-making process or in the nished tissue product. Lint/dust generation has an overall negative impact across tissue paper manufacturing and handling operations, causing safety hazards, machine runnability di culties, and product quality issues. To date, there are no well-established industry standards to quantify dusting/linting propensities in nished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Tissue paper products, in general, can release extremely high concentrations of dust (fibers with a length approximately 0.4 to 2.0 mm) and lint (fibers with a length approximately 4.0 to 5.0 mm and a width of 500 μm), which are encountered during stages of processing and packaging (Baum 2001;Frazier et al 2022). In the manufacturing process of this type of product, these fibers and dust accumulate on the surface of the paper and in the elements of the converting machines, which translates into product quality problems and difficulties in runnability, and later, in the usage of the final consumer (Kuryllowicz 1984;Linder et al 2017).…”
Section: Dusting and Lintingmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue paper products, in general, can release extremely high concentrations of dust (fibers with a length approximately 0.4 to 2.0 mm) and lint (fibers with a length approximately 4.0 to 5.0 mm and a width of 500 μm), which are encountered during stages of processing and packaging (Baum 2001;Frazier et al 2022). In the manufacturing process of this type of product, these fibers and dust accumulate on the surface of the paper and in the elements of the converting machines, which translates into product quality problems and difficulties in runnability, and later, in the usage of the final consumer (Kuryllowicz 1984;Linder et al 2017).…”
Section: Dusting and Lintingmentioning
confidence: 99%
“…This lint and dust accumulation form agglomerates on the surface of the tissue paper sheet, and consequently decreases its softness with a roughness increase. Due to this fact, the usage of these products contaminated by lint and dust becomes unpleasant, such that the product does not meet the requirements of the final consumer (Frazier et al 2022). The fishbone diagram presented in Fig.…”
Section: Dusting and Lintingmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al (2022) used SEM for the characterization of the fibre lumen collapsibility due to different refining energy. A qualitative analysis of the cross-section based on SEM images was published by Frazier et al (2022) to evaluate the impact of dust particles on the fibre network. Morais et al (2021) showed the densification effect of microfibrillated cellulose (MFC) as an additive in tissue paper using cross-sectional SEM images.…”
Section: Introductionmentioning
confidence: 99%